Neuroimaging findings in a case of autosomal recessive cutis Laxa syndrome: a case report - Tanwar, Rekha; Singh, Shahsi Kumar; Kaur, Maninder (International Journal of Contemporary Pediatrics, 2025)
Cutis laxa is a heterogeneous group of inherited and acquired connective tissue disorders characterized by a loose skin and variable systemic involvement. One Autosomal dominant and three autosomal recessive forms of cutis laxa have been described. The diagnosis of CL syndrome is based on clinical assessment of typical skin features and the associated extracutaneous finding. Magnetic resonance imaging of brain in evaluation of cutis laxa syndrome has not been described in literature till date. We describe MR neuroimaging in a case of type 2 AR cutis laxa syndrome.